UV-VIS Curable PEG Hydrogels for Biomedical Applications with Multifunctionality - Tina Sabel-Grau; Arina Tyushina; Cigdem Babalik; Marga C. Lensen (Gels, 2022)
Multifunctional biomedical materials capable of integrating optical functions are highly desirable for many applications, such as advanced intra-ocular lens (IOL) implants. Therefore, poly(ethylene glycol)-diacrylate (PEG-DA) hydrogels are used with different photoinitiators (PI). In addition to standard UV PI Irgacure, Erythrosin B and Eosin Y are used as PI with high sensitivity in the optical range of the spectrum. The minimum PI concentrations for producing new hydrogels with PEG-DA and different PIs were determined. Hydrogel films were obtained, which were applicable for light-based patterning and, hence, the functionalization of surface and volume. Cytotoxicity tests confirm cytocompatibility of hydrogels and compositions. Exploiting the correlation of structure and function allows biomedical materials with multifunctionality.